Drug-eluting balloon: Very short-term exposure and overlapping - Cremers, Bodo; Speck, Ulrich; Kaufels, Nicola; Mahnkopf, Dirk; Kühler, Michael; Böhm, Michael; Scheller, Bruno (Thrombosis and Haemostasis, 2009)
Paclitaxel balloon coating has shown promising effects in inhibiting restenosis in initial clinical trials. The aim of the present study was to evaluate the influence of two critical features of drug-eluting balloon (DEB) application – inflation time and increased dose due to overlapping balloons. Fifty-six stainless steel stents were implanted in the left anterior descending and circumflex coronary arteries of 28 domestic pigs using a 1.2:1.0 overstretch ratio. Stents were mounted on conventional un-coated and paclitaxel-coated angioplasty balloon catheters. The animals were randomized to five different treatments with a range of short (10 seconds [s] inflation using 1 DEB) to extended (2x60 s inflation using 2 DEB) intima contact time. After 28 days, quantitative angiography and histomorphometry of the stented arteries was performed on a total of 23 pigs. Paclitaxel balloon coating led to a marked reduction of parameters characterizing in-stent stenosis: Late lumen loss was 1.37 ± 0.49 mm for uncoated balloons, 0.23 ± 0.42 mm for one coated balloon 60 s inflation time, 0.37 ± 0.28 mm for 10 s inflation time and 0.30 ± 0.19 mm for the vessel segment treated by two coated balloons with 60 s inflation each. Neointimal areas were 4.26 ± 1.18, 1.68 ± 0.23, 1.83 ± 0.40 and 1.67 ± 0.46 mm², respectively (p=0.001 versus control, p>0.05 between paclitaxel-treated groups). Despite the marked reduction of neointimal proliferation, endothelialization of stent struts was present in all samples. DEB were found to effectively reduce neointimal proliferation regardless of inflation time and dose within the tested range. No adverse reactions were seen as dose was increased to more than three times the clinically tested dose.
Keywords: Restenosis; drug-eluting balloon; inflation time; overlap; paclitaxel